2004
DOI: 10.1634/stemcells.2004-0127
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐Like Growth Factor Promotes Engraftment, Differentiation, and Functional Improvement after Transfer of Embryonic Stem Cells for Myocardial Restoration

Abstract: Insulin-like growth factor-1 (IGF-1) promotes myocyte proliferation and can reverse cardiac abnormalities when it is administered in the early fetal stage. Supplementation of a mouse embryonic stem cell (ESC) suspension with IGF-1 might enhance cellular engraftment and host organ-specific differentiation after injection in the area of acute myocardial injury. In the study reported here, we sought to enhance the restorative effect of ESCs in the injured heart by adding IGF-1 to the injected cell population. Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(74 citation statements)
references
References 26 publications
2
70
1
1
Order By: Relevance
“…44 IGF-1 promotes engraftment, differentiation, and functional improvement after transfer of embryonic stem cells for myocardial restoration. 16 Urbanek and coworkers found that resident cardiac stem cells express the IGF-1R, 15 and our present data demonstrate expression of a functionally active IGF-1R in EPC. ϩ -derived EPC, freshly isolated CD133 ϩ / VEGFR2 ϩ EPC and rescue of impaired function of EPC derived from elderly subjects by IGF-1.…”
Section: Thum Et Al Igf-1 Corrects Impairment Of Epc 439supporting
confidence: 73%
See 1 more Smart Citation
“…44 IGF-1 promotes engraftment, differentiation, and functional improvement after transfer of embryonic stem cells for myocardial restoration. 16 Urbanek and coworkers found that resident cardiac stem cells express the IGF-1R, 15 and our present data demonstrate expression of a functionally active IGF-1R in EPC. ϩ -derived EPC, freshly isolated CD133 ϩ / VEGFR2 ϩ EPC and rescue of impaired function of EPC derived from elderly subjects by IGF-1.…”
Section: Thum Et Al Igf-1 Corrects Impairment Of Epc 439supporting
confidence: 73%
“…15 Likewise, in the infarcted myocardium, IGF-1 promotes engraftment, differentiation, and function of implanted embryonic stem cells leading to improved myocardial function. 16 IGF-1 transgenic mice demonstrate increased telomerase activity and preservation of cardiac resident stem cells. 10 The effects of IGF-1 on EPC homeostasis and function are not known.…”
mentioning
confidence: 99%
“…In view of the risks associated with the broad differentiation potential of ESCs in vivo, only sporadic reports employed these cells in their uncommitted state to repair the damaged heart (203,243,244,312,313,509). In sharp contrast to the pluripotency of ESCs, cardiomyocytes were detected, but capillary structures and resistance arterioles were not found.…”
Section: A Human Embryonic Stem Cellsmentioning
confidence: 99%
“…IGF-1 overexpression increases cardiac stem cell number and growth, leading to an increase in myocyte turnover and function in the aging heart (6). After infarction, IGF-1 promotes engraftment, differentiation, and functional improvement of embryonic stem cells transplanted into myocardium (7). However, IGF-1 is a small protein that diffuses readily through tissues, a property that allows it to signal over great distances (8), but this property could restrict its retention within a tissue for prolonged periods.…”
mentioning
confidence: 99%